A finite element solution to the generalized Onsager model of fluid flow in a countercurrent gas centrifuge. Issue 11 (23rd July 2020) - Thomas, Benjamin R.; Witt, William C.; Paudel, Wisher; Wood, Houston G.
ABSTRACT: Based on the Onsager Equation, a linearized sixth-order partial differential equation describing the flow in the volume of the rotor of a gas centrifuge is solved using a finite element algorithm employed by the CurvSOL code. The results are compared to those from Pancake, an existing code that uses eigenfunction expansion to solve the Onsager equation. Excellent agreement is demonstrated between the solutions of the wall temperature gradient and scoop drive mechanisms for both the Rome and Iguaçu centrifuge designs. Results suggest rotor speed and radius play key roles in the influence of wall curvature on the flow solution.